Depot Medroxyprogesterone Acetate Use Is Associated With Elevated Innate Immune Effector Molecules in Cervicovaginal Secretions of HIV-1–Uninfected Women. (1st May 2015) - Guthrie, Brandon L.; Introini, Andrea; Roxby, Alison C.; Choi, Robert Y.; Bosire, Rose; Lohman-Payne, Barbara; Hirbod, Taha; Farquhar, Carey; Broliden, Kristina
Abstract : Objective: The effects of sex hormones on the immune defenses of the female genital mucosa and its susceptibility to infections are poorly understood. The injectable hormonal contraceptive depot medroxyprogesterone acetate (DMPA) may increase the risk for HIV-1 acquisition. We assessed the local concentration in the female genital mucosa of cationic polypeptides with reported antiviral activity in relation to DMPA use. Methods: HIV-1–uninfected women were recruited from among couples testing for HIV in Nairobi, Kenya. Cervicovaginal secretion samples were collected, and the concentrations of HNP1–3, LL-37, lactoferrin, HBD-2, and SLPI were measured by enzyme-linked immunosorbent assays. Levels of cationic polypeptides in cervicovaginal secretions were compared between women who were not using hormonal contraception and those using DMPA, oral, or implantable contraception. Results: Among 228 women, 165 (72%) reported not using hormonal contraception at enrollment, 41 (18%) used DMPA, 16 (7%) used an oral contraceptive, and 6 (3%) used a contraceptive implant. Compared with nonusers of hormonal contraception, DMPA users had significantly higher mean levels of HNP1–3 (2.38 vs. 2.04 log10 ng/mL; P = 0.024), LL-37 (0.81 vs. 0.40 log10 ng/mL; P = 0.027), and lactoferrin (3.03 vs. 2.60 log10 ng/mL; P = 0.002), whereas SLPI and HBD-2 were similar. Conclusions: Although all analyzed cationic polypeptides have intrinsic antiviral capacity, their interaction and cumulative effect on female genital mucosa susceptibility to infections in vivo has yet to be unraveled. This study suggests a potential mechanism underlying the effect of DMPA on the innate immune defenses, providing a rationale to investigate its effect on HIV-1 acquisition risk. Abstract : Supplemental Digital Content is Available in the Text.